Development and Validation of Computational Thinking Assessment of Chinese Elementary School Students. (August 2021) - Li, Yan; Xu, Shan; Liu, Jia
Recent advances in artificial intelligence have brought attention to computational thinking (CT) in school education worldwide. However, little is known about the development of the literacy of CT in children, mainly because of the lack of proper psychometric assessments. We developed the first psychometrically validated assessment on the literacy of CT of children in Chinese elementary schools, coined as the Computational Thinking Assessment for Chinese Elementary Students (CTA-CES). Items were constructed to reflect key aspects of CT such as abstraction, algorithm thinking, decomposition, evaluation, and pattern recognition. To examine the test reliability and validity, we recruited two samples of 280 third- to sixth-grade students in total. Cronbach's alpha provided evidence for the reliability of the test scores, item response theory analyses demonstrated psychometric appropriateness, whereas construct validity was verified by convergent validity, and criterion-related validity was confirmed by correlations between the CTA-CES and measures related to CT, namely reasoning, spatial ability, and verbal ability. In addition, an fMRI study further demonstrated similar neural activation patterns when students conducted the CTA-CES and programming tasks. Taken together, the CTA-CES is the first reliable and valid instrument for measuring the literacy of CT for Chinese children, and may be applicable to children worldwide.